(untitled) (Texas Journal of Agriculture and Biological Sciences, 2025)
The article notes that in soil-climatic conditions of Andijan region under different planting dates of 45-day seedlings of onion-shallot variety Sprint marketable yield was at the planting date of February 10 (control) - 48.9 t/ha, February 20 - 40.4 t/ha, March 1 - 32.5 t/ha and March 10 - 25.0 t/ha, as well as the share of marketable yield in the total yield was 87.0; 86.7; 83.5 and 79.1%, respectively